The utilization of ethanol for production of 1-butanol catalysed by Li-Al mixed metal oxides enhanced by Cu - Frolich, Karel; Malina, Jan; Hájek, Martin; Kocik, Jaroslav (Elsevier, 2024)
The selective catalytic conversion of bio-ethanol into valuable chemical compounds, particularly 1-butanol (i.e., Guerbet reaction), has gained significant attention due to its potential to replace fossil sources in the future. This work continues the search for a catalyst with high ethanol conversion and selectivity toward desired products. The novelty of the study lies in its use of copper-lithium-aluminum mixed metal oxides as heterogeneous catalysts. Li-Al oxides were prepared via urea precipitation, and copper was introduced in two ways: (i) during coprecipitation and (ii) post-synthetic impregnation. Gas-phase reaction in a fixed-bed reactor was realized at varying temperatures and pressures. The properties of the mixed metal oxides proved to be crucial, as a wide range of products was observed. Catalysts that shifted from acidic to basic properties, and those with different redox properties, significantly affected ethanol conversion and selectivity toward the desired higher alcohols. Compared to previously used magnesium-aluminum mixed metal oxides, a lower amount of copper was required to achieve similar or higher ethanol conversion (71 %) and butanol selectivity (30 %) at 300-350 degrees C and 10 MPa. Thus, lithium-aluminum mixed metal oxides showed the potential to surpass magnesium-aluminum mixed metal oxides with further study and adjustment of their properties.
Využití etanolu pro výrobu 1-butanolu katalyzovanou Li-Al směsnými oxidy kovů zesílenými Cu
Keywords: Ethanol; Guerbet reaction; Mixed metal oxide; Lithium; Aluminium; Copper; etanolu; 1-butanolu; katalýza; Li-Al směsné oxidy; Cu